Finance and Management for the Anthropocene. (March 2019) - Shrivastava, Paul; Zsolnai, Laszlo; Wasieleski, David; Stafford-Smith, Mark; Walker, Thomas; Weber, Olaf; Krosinsky, Cary; Oram, David
The Anthropocene era is characterized by a pronounced negative impact of human and social activities on natural ecosystems. To the extent finance, economics and management underlie human social activities, we need to reassess these fields and their role in achieving global sustainability. This article briefly presents the scientific evidence on accelerating impacts of human activities on nature, which have resulted in breach of planetary boundaries and onset of global climate change. It offers some potential leverage points for change toward sustainability stewardship by highlighting the important role of finance and economics in addressing climate change. We examine the role of financial stakeholders in addressing planetary boundaries and offer a modified stakeholder theory, from which we propose future directions for finance in the Anthropocene.